2022
DOI: 10.1051/0004-6361/202142720
|View full text |Cite
|
Sign up to set email alerts
|

Planet populations inferred from debris discs

Abstract: We know little about the outermost exoplanets in planetary systems because our detection methods are insensitive to moderate-mass planets on wide orbits. However, debris discs can probe the outer-planet population because dynamical modelling of observed discs can reveal properties of perturbing planets. We use four sculpting and stirring arguments to infer planet properties in 178 debris-disc systems from the ISPY, LEECH, and LIStEN planet-hunting surveys. Similar analyses are often conducted for individual di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 240 publications
(300 reference statements)
0
58
1
Order By: Relevance
“…Recent work by Pearce et al (2022) found, after adopting an inner disk radius for the AU Mic system of 28.7 ± 0.3 au, that a planet with a mass of 0.44 ± 0.03 M Jup and semimajor axis of 21.9 ± 0.3 au would be able to "sculpt" the inner part of the AU Mic debris disk. Since our model yields a different inner radius than in Pearce et al (2022), we recalculated this planet mass and radius using their publicly available code, 13 finding that a planet with a minimum mass of 0.34 ± 0.03 M Jup and maximum semimajor axis of -+ 17.0 0.3 0.7 au would be able to truncate the inner part of the disk that is modeled in this work.…”
Section: Radial Structurementioning
confidence: 99%
“…Recent work by Pearce et al (2022) found, after adopting an inner disk radius for the AU Mic system of 28.7 ± 0.3 au, that a planet with a mass of 0.44 ± 0.03 M Jup and semimajor axis of 21.9 ± 0.3 au would be able to "sculpt" the inner part of the AU Mic debris disk. Since our model yields a different inner radius than in Pearce et al (2022), we recalculated this planet mass and radius using their publicly available code, 13 finding that a planet with a minimum mass of 0.34 ± 0.03 M Jup and maximum semimajor axis of -+ 17.0 0.3 0.7 au would be able to truncate the inner part of the disk that is modeled in this work.…”
Section: Radial Structurementioning
confidence: 99%
“…surface area, relative to the star (2×10 −4 ) (Moór et al 2006). Herschel PACS observations at 70 and 160 µm marginally resolved a bright ring with radius ∼ 54 AU and width 39 AU that appeared elongated to the NW and SE (Marshall et al 2021;Pearce et al 2022). However, due to Herschel's poor spatial resolution the exact geometry of the disk remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The current structure of these debris belts has largely been shaped by their interaction with the surrounding planets, not only through the violent clearing of the orbital paths, but also through more subtle resonant and secular processes. Similarly, we expect that the structure of extrasolar debris belts can help us infer the presence of planetary perturbers and their dynamical E-mail:lbr63@cornell.edu history (e.g., Raymond et al 2011;Pearce et al 2022;Guo & Kokubo 2022).…”
Section: Introductionmentioning
confidence: 99%